Crowned Dens Syndrome Triggered by Dental Treatment - Satoru Morita; Yuki Otsuka; Yohei Masuda; Yoshiaki Soejima; Fumio Otsuka (Clinical Case Reports)
ABSTRACT Crowned dens syndrome (CDS) is an important yet often overlooked cause of fever and neck pain, frequently leading to unnecessary examinations and treatments and misdiagnosis as infectious diseases or rheumatic diseases. The mechanism of an acute attack of CDS is not clarified completely, while it is considered that severe systemic stress can trigger inflammation caused by calcium pyrophosphate crystals. We describe a case of CDS triggered by localized physical stress to the neck and emphasize the importance of considering this condition in cases of fever and neck pain following dental treatment.